Analisis Situasi dalam Pengembangan Kurikulum - Musfira, Nurul; Fikri, Muhammad Nurul; Ramadhani, Fitriah; Saleh, Sirajuddin (Indo-MathEdu Intellectuals Journal, 2025)
Curriculum development today does not only focus on determining learning objectives and materials, but also emphasises the importance of situation analysis as a preliminary step that determines the direction, relevance, and success of the curriculum. This article aims to explain the essence and role of situation analysis in the curriculum development process. This study uses a literature review method by examining various relevant literature. The results of the study show that situation analysis plays a crucial role in ensuring that the curriculum is appropriate to the needs of students and the educational context. In addition, the successful implementation of the curriculum is influenced by several factors, including the leadership of the school principal, teacher competence, student activity, the availability of facilities and learning resources, and the support of the school committee. Curriculum implementation will be effective if all these factors can collaborate and support each other synergistically.